The Impact Of Monetary Union On Regional Integration In West Africa - Olaiwola, Jimoh Sodiq (2022)
This study investigates the effect of monetary union on regional integrations in a panel sample of 16 West African countries over the period of 1980 – 2020 using a dynamic factor model along with the estimates of Driscoll-Kraay and panel autoregressive distributive lag model. Firstly, it examines the feasibility of a common currency in the West African region. Secondly, it analyzes the effect of common currency on the intra-regional trade integration in the West African region. Thirdly, it assesses the effect of common currency on the financial integration in the West African region. Evidence from the dynamic factor model reveal that Guinea, Guinea Bissau, Mali, Sierra Leone, and Togo respond similarly to common regional and idiosyncratic factors in the West African region. Thus, these countries constitute the core countries for the proposed union.